Building a Methodology for the Learning of English in Rural Context: Learners Insights - Dover-Carrillo, Yendry (2019)
This article shows the results of a research and university extension project carried out at the Chorotega campus of the Universidad Nacional, Costa Rica, titled Constructing an innovative methodology that favors English learning in people with low schooling in rural areas of the Gulf of Nicoya and the Chorotega Region, Costa Rica. (Rosales, Vidaurre y Dover, 2013-2015). The purpose was to show how the participants’ insights contribute to the design of a teaching-learning approach for English  learning in  non-traditional contexts. A qualitative study was conducted with a descriptive, interpretive design. In this study, the 30 participants became active informants in the research process carried out before, during and after the training; they came from the rural areas of the Gulf of Nicoya and the Chorotega Region. The data was collected using three instruments: observation, semi-structured interviews, and focus groups. The findings showed that the incorporation of the observations and suggestions, exposed by the learners, influenced the process of acquisition of the target language and favored the selection of linguistic, social, and contextual content according to the learners’ reality.